Comparison of Interpretation Between CPT and Res-2d Methods for Geostratigraphic Profiling Determination of Kota Depok - et.al, Putera Agung Maha Agung , (Jurnal Semesta Teknika, 2012)
In its simplest application, the cone penetrometer offers a quick, expedient, and economical way to profiling a subsurface soil layering at a particular site. No drilling, soil samples, or spoils are generated, therefore, cone penetration test CPT is less disruptive from an environmental standpoint. The continuous nature of CPT reading permits clear delineations of various soil strata, their depths, thicknesses, and extent, perhaps better than conventional rotary drilling operations that use a standard drive sampler at 5-ft vertical intervals. The cone penetrometer is instrumented with load cells to measure point stress and friction during a constant rate of advancement. The results can be interpreted within different theoretical frameworks or by using empirical methods, or both. RES-2D (resistivity â two dimension) completed by Geoscanner devices is applicable to interpret the soil profiling from soil exploration works. Generally, the geoscanner is used to assess the geological subsurface condition for mining works. This paper is addressed to compare the results for soil classification in Kota Depok, West Java using a cone penetration test and RES-2D. From both methods, the result of soil strata shows the soft soil in study area can be classified as clay layers from ground surface to the depth of 15.0 m. However, the CPT is less applicable to measure exactly the elevation of ground water table than RES-2D. In addition, RES-2D is also less applicable to predict the soil properties of the soil type than CPT. In general application, both devices can be applied to soil investigation for geotechnical works.Â  Â